Clinical and epidemiological characteristics of pediatric cataract in a Latin American population - Adriana Andrea Solano Franco; Adriana Restrepo; Diana M. Sierra; Ana Maria Gomez (The Pan-American Journal of Ophthalmology)
Introduction: Cataract is defined as the opacity of the lens, which leads to reduced vision and can eventually result in blindness. In pediatric patients, it has a poor visual prognosis if not diagnosed early. Objective: The aim of our study is to clinically and demographically characterize pediatric cataract patients in a referral hospital of a developing country, as well as to identify the challenges faced in providing care for these patients. Subjects and Methods: A cross-sectional descriptive observational study was conducted, including all pediatric patients diagnosed with cataract over a 10-year period. Results: A total of 95 patients were studied, comprising 113 eyes. The most common clinical presentation was leukocoria. The median age at diagnosis was 24 months (interquartile range [IQR]: 80 months), and the median time from diagnosis to surgery was 1 month (IQR: 2 months). The median follow-up time after surgery was 3 months (IQR: 1–12 months). The most common cause of loss to follow-up was financial or personal difficulties faced by the parents, accounting for 20% of cases. Conclusions: Red reflex examination is essential during pediatric visual screening to ensure early diagnosis of cataract. The age at diagnosis varies depending on the etiology and may be influenced by socioeconomic status and local factors such as access to healthcare services.